School locations and gender variables on students’ science process skills as a predictor of academic achievement in senior secondary school - Maxwell Chukwunazo Obikezie; Ekoyo Destiny Onyebuch; Esther Ebele Akachukwu; Henrietta Obioma Nnalue (S&Co Publishing, 2025)
This study examined school locations and gender variables on students’ science process skills as a predictor of academic achievement in senior secondary school. Guided by two research objectives and two hypotheses tested at the 0.05 level of significance, the study employed a correlational survey design. The population of the study comprised 2720 senior secondary two (SS2) students offering biology, chemistry, data processing, physics and mathematics in all the public secondary schools in Onitsha Education Zone. A Sample size of 408 SS 2 students offering biology, chemistry, data processing, physics and mathematics in the Education Zone was drawn using multistage procedure. Students Science Process Skills Scale (SSPSS) and the achievement scores which was obtained from biology, chemistry, data processing, physics and mathematics teachers’ grade book for 2023/2024 academic session from the sampled schools were used as instruments for data collection. The instruments were validated by three experts. The reliability of SSPSS was established using Cronbach alpha method. The reliability coefficient of SSPSS was found to be 0.73. Data from SSPSS and academic scores were collected; analysis involved correlation coefficients (R, R²) and regression ANOVA to answer research questions and test hypotheses. The study revealed low predictive value of students’ science process skills on academic achievement in science for both urban and rural schools, regardless of gender. Science process skills are not significant predictors of students’ achievement in both school locations and gender based. From the findings recommendations and conclusions were made.